2022
DOI: 10.3390/antiox11071298
|View full text |Cite
|
Sign up to set email alerts
|

Preharvest Methyl Jasmonate Treatment Increased Glucosinolate Biosynthesis, Sulforaphane Accumulation, and Antioxidant Activity of Broccoli

Abstract: Broccoli is becoming increasingly popular among consumers owing to its nutritional value and rich bioactive compounds, such glucosinolates (GSLs) and hydrolysis products, which are secondary metabolites for plant defense, cancer prevention, and higher antioxidant activity for humans. In this study, 40 μmol/L methyl jasmonate (MeJA) was sprayed onto broccoli from budding until harvest. The harvested broccoli florets, stem, and leaves were used to measure the contents of GSLs, sulforaphane, total phenolics, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
2
5
0
Order By: Relevance
“…The results revealed that the preharvest MeJA treatment resulted in a significant increase in the antioxidant capacity of radish microgreens across all cultivars. Similar findings were reported by Wang et al [ 9 ] in a study of two cultivars of broccoli florets, where MeJA treatment also showed a remarkable increase in antioxidant capacity. Among the radish microgreens, ‘Asia purple’ treated with 1.0 mM MeJA exhibited the highest antioxidant activity, and ‘Koregon red’ showed the second highest in all assays when the sample concentrations were 1 and 2.5 mg mL −1 ( Table 4 ).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The results revealed that the preharvest MeJA treatment resulted in a significant increase in the antioxidant capacity of radish microgreens across all cultivars. Similar findings were reported by Wang et al [ 9 ] in a study of two cultivars of broccoli florets, where MeJA treatment also showed a remarkable increase in antioxidant capacity. Among the radish microgreens, ‘Asia purple’ treated with 1.0 mM MeJA exhibited the highest antioxidant activity, and ‘Koregon red’ showed the second highest in all assays when the sample concentrations were 1 and 2.5 mg mL −1 ( Table 4 ).…”
Section: Resultssupporting
confidence: 90%
“…This observation highlights the potential of 1.0 mM MeJA treatment to enhance the accumulation of these specific GSLs. A previous study on chives showed the dose-dependent effects of preharvest MeJA treatment on secondary metabolites [ 9 ], and 0.5 mM MeJA had the most significant effect, specifically on phenolic compounds of substrate-grown chives.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to a previously described method [ 80 ], GSLs were extracted and quantified using the following steps. Briefly, the freeze-dried sample powder was soaked in 70% methanol with 100 μl of sinigrin (5 mmol/l, internal standard) for 20 min in a 75°C water bath, the cooling mixture added with barium acetate and then for centrifugation.…”
Section: Methodsmentioning
confidence: 99%